Phytochemical Analysis And Bioactivity Evaluation Of Standardized Extracts Of Mitragyna Speciosa And Pharmacokinetics Of Mitragynine - Parthasarathy, Suhanya (2010)
The pharmacology of M. speciosa leaf extracts and mitragynine in rats were investigated. Two new High Performance Liquid Chromatography Ultraviolet HPLC –UV analytical methods were developed and validated for assay of mitragynine in M. speciosa leaf extracts and plasma. Both HPLC-UV method for assay of mitragynine in plant matrix and plasma yield a clean chromatogram, short analysis time, good assay sensitivity and was successfully used for their intended applications. The first HPLC-UV method was used to standardize water , methanolic and alkaloid extracts of M. speciosa leaf which was subsequently used for antimicrobial and antioxidant studies.